Syntheses of 7a-Substituted Pyrrolizidine Derivatives via Stereocontrolled Anionic Cyclization - Ming, Hongjun; He, Darong; Si, Shengmeng; Xu, Chao; Yuan, Yunge; Tian, Xiaoran; Hu, Zhigang; Li, Shikuo; Zhang, Hui; Huang, Fangzhi; Chen, Yue-Lei (Synthesis, 2024)
Starting from inexpensive proline and epichlorohydrin, a pivotal stereocontrolled anionic cyclization reaction paves the way for a robust and adaptable methodology to produce stereoisomers of 7a-substituted pyrrolizidine derivatives. This process yields intriguing 7a-hydroxymethyl pyrrolizidine derivatives, among them valuable trans-(2-fluorohexahydro-1H-pyrrolizin-7a-yl)methanol, which is attainable through multiple steps.
Keywords: pyrrolizidine alkaloids; 7a-substituted pyrrolizidine; stereocontrolled synthesis; anionic cyclization; total synthesis